Comparative analysis between PUMA and CAPTURE questionnaires for chronic obstructive pulmonary disease (COPD) screening in smokers - Sebayang, Risa RB.; Pandia, Pandiaman; Pradana, Andika; Tarigan, Amira P.; Wahyuni, Arlinda S. (Narra J, 2024)
Chronic obstructive pulmonary disease (COPD) presents a significant global challenge, impacting health systems, economies, and societies. Its prevalence is anticipated to rise owing to an aging demographic. Although the PUMA and CAPTURE questionnaires are available for COPD screening, their comparative effectiveness has not been studied in Indonesia. The aim of this study was to evaluate the effectiveness of the PUMA and CAPTURE questionnaires as screening tools for COPD among smokers. A cross-sectional study was conducted at Universitas Sumatera Utara Hospital and H. Adam Malik General Hospital, Medan, Indonesia, from December 2022 to February 2023. Smokers aged over 40 or above with a history of smoking more than 100 cigarettes in their lifetime and no previous COPD diagnosis were included in the study. To collect the responses to PUMA and CAPTURE questionnaire, face-to-face interviews were conducted, followed by a spirometry test. A total of 76 smokers were included in the study; the predominant age group was 51–60 years (36.8%), with the majority being male (81.6%). Most participants began smoking at ages 15−20 years (65.8%) and had been smoking for 20–30 years (36.8%) at a moderate intensity (44.8%). Spirometry tests indicated obstructive patterns in 50 participants, with 17 classified as severe obstruction. At a cut-off score of ≥6, the PUMA questionnaire yielded a sensitivity of 72.55% and a specificity of 84%. In contrast, the CAPTURE questionnaire, with a cut-off score of ≥4, exhibited a sensitivity of 70.83% and a specificity of 64.29%. These results imply that the PUMA questionnaire could be more efficient in COPD screening compared to the CAPTURE questionnaire.